2021
DOI: 10.1186/s40594-021-00289-w
|View full text |Cite
|
Sign up to set email alerts
|

Students’ implicit epistemologies when working at the intersection of engineering and the arts

Abstract: Background This paper explores the epistemologies and discourse of undergraduate students at the transdisciplinary intersection of engineering and the arts. Our research questions focus on the kinds of knowledge that students value, use, and identify within an interdisciplinary digital media program, as well as how they talk about using these epistemologies while navigating this transdisciplinary intersection. Six interviews were conducted with students pursuing a semester-long senior capstone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The makerspace of the School of Civil Engineering became the space for tinkering and the corresponding development of such activities. Makerspaces have become increasingly common venues of STEM and STEAM education and are rapidly being incorporated into undergraduate programs [33][34][35][36][37]. These spaces give students and instructors access to advanced design technology and facilitate the incorporation of a wide variety of projects into the curriculum.…”
Section: Literature Review: the Role Of Makerspacesmentioning
confidence: 99%
“…The makerspace of the School of Civil Engineering became the space for tinkering and the corresponding development of such activities. Makerspaces have become increasingly common venues of STEM and STEAM education and are rapidly being incorporated into undergraduate programs [33][34][35][36][37]. These spaces give students and instructors access to advanced design technology and facilitate the incorporation of a wide variety of projects into the curriculum.…”
Section: Literature Review: the Role Of Makerspacesmentioning
confidence: 99%
“…In addition to courses in higher education, STEM-based engineering curricula is promoted by many countries in K-12 education (Chien & Chu, 2018;Cruz et al, 2021) because engineering design experiences have played an increasingly substantive role in precollege students' STEM education and career preparation in recent years (Crismond & Adams, 2012). K-12 education studies have found that technology-learning activities based on engineering design enhance STEM learning (Lin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To cultivate science, technology, engineering, and mathematics (STEM) competence, skills, and interest among students in the 21st century, governments worldwide have supported policy initiatives that promote STEM education with engineering design (ED) in secondary schools as a bridge to higher-level STEM fields (Chien and Chu, 2018 ; Cruz et al, 2021 ; Kutnick et al, 2020 ). This STEM-ED assists students in choosing future careers, motivates students to learn, and facilitates their interest in (and integration of) STEM subjects (Kwon, 2016 ).…”
Section: Introductionmentioning
confidence: 99%